ACTIVITY OF MUSEUMS AND DEVELOPMENT OF TOURISM IN UZBEKISTAN - Noyibjon Marufjonovich Khudoyorov (Journals Park Publishing, 2023)
This article focuses on the development of tourism, its promotion to the general public, the focus on tourism, the decisions and regulations of the President in the field of tourism in Uzbekistan and provides information on the role of museums, ancient monuments and shrines, material and cultural monuments in the development of tourism as well.
Keywords: tourism, museum, economy, ecotourism, knife-making, local handicrafts.